Cinderella - Lewis, Shari; Caminos, Jane, 1947- (New York : Bantam Books, 1994)
Although mistreated by her stepmother and stepsisters, Cinderella meets her prince with the help of her fairy godmother.
"A little rooster book."
Keywords: Fairy tales; Folklore; Literary recreations